2021
DOI: 10.3390/ijerph182211811
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Socio-Demographic Factors Affecting Psychological Symptoms in Humidifier Disinfectant Survivors

Abstract: This study aimed to compare the psychological symptoms of humidifier disinfectant survivors to the general population and explore socio-demographic factors influencing survivors’ psychological symptoms. A one-way Multivariate Analysis of Covariance (MANCOVA) and a series of two-way MANCOVA were conducted with a sample of 228 humidifier disinfectant survivors and 228 controls. The results demonstrated that the survivor group displayed higher anxious/depressed symptoms, withdrawn symptoms, somatic complaints, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These individuals presented maladaptive functioning in life adjustment (i.e., low scores on relationships with Friends and Partners and Job Adjustment). These results show how painfully humidifier disinfectant survivors suffer from a myriad psychological problems ( Ko et al, 2021 ). These results are consistent with those of previous studies (e.g., Dell’Osso et al, 2012 ; Lee et al, 2017 ; Tian et al, 2020 ) that reported a significant relationship between psychological symptoms (e.g., posttraumatic stress symptoms, depression, and anxiety) and maladaptive behaviors (e.g., problematic Internet use, alcohol or drug abuse, no self-scare, risk-taking behavior, and negative coping) among the sample of disaster survivors.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These individuals presented maladaptive functioning in life adjustment (i.e., low scores on relationships with Friends and Partners and Job Adjustment). These results show how painfully humidifier disinfectant survivors suffer from a myriad psychological problems ( Ko et al, 2021 ). These results are consistent with those of previous studies (e.g., Dell’Osso et al, 2012 ; Lee et al, 2017 ; Tian et al, 2020 ) that reported a significant relationship between psychological symptoms (e.g., posttraumatic stress symptoms, depression, and anxiety) and maladaptive behaviors (e.g., problematic Internet use, alcohol or drug abuse, no self-scare, risk-taking behavior, and negative coping) among the sample of disaster survivors.…”
Section: Discussionmentioning
confidence: 86%
“…Among the victims, 57.5% experienced depression, 55.1% experienced guilt and self-blame, 54.3% were anxious, 27.6% had suicidal thoughts, and 11% attempted suicide ( Leem et al, 2020 ). Ko et al (2021) compared the mental health status of 228 victim-survivors with 228 members of the general population from 2018 to 2021. They reported that victim survivors had much higher scores on anxiety, depression, atrophy, physical discomfort, thinking problems, attention problems, and aggressive behavior than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…For group 1, studies published on humans, a total of 49 articles were selected ( Table 2 ). 1 2 3 4 5 6 7 9 10 11 12 13 14 17 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 The suspicion that humidifier disinfectant might be a cause of lung damage was suggested in 2011. Studies in international journals began to appear in 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Case reports, panel survey-based studies, and cross-sectional studies have been conducted on the damage to the neuropsychiatric system in cases of non-respiratory damage. 36 37 38 …”
Section: Resultsmentioning
confidence: 99%
“…According to Leem et al [16], 57.5% of humidifier disinfectant survivors reported depression, 55.1% reported guilt and self-blame, 54.3% reported anxiety, 27.6% reported suicidal thoughts, and 11% reported suicide attempts. Ko et al [17] compared the mental health status of humidifier disinfectant survivors from 2018 to 2021 in a general population of 228, and the survivors reported more psychological problems, such as anxiety, depression, atrophy, and thinking problems, compared to the general population.…”
Section: Introductionmentioning
confidence: 99%